Pengguna Dadah Wanita di Malaysia: Pengalaman Penagihan dan Hubungan Kekeluargaan (Sains Humanika, 2014)
Women involvement in drug abuse has adverse impacts not only to the nation but also impose great challenges to achieve stable family structures. Therefore, this article aims to explore the experiences of women drug user in Malaysia with reference to their drug abuse activity and identify the level of family relationship they possess. This research used quantitative method and cross-sectional survey. A total of 120 women at the Center of Drugs Recovery and Narcotic Rehabilitation (PUSPEN), Bachok, Kelantan were chosen using stratified random sampling. Data were analyzed using descriptive analysis. The results of the study showed that 39.5 percent of women inmates started getting involved in drug activities at the age of 15-20 years, 79 percent had been arrested for the first time to undergo a rehabilitation process, majority of them (54.6 percent) reported to use drugs on regular basis and more than half of the respondents (63 percent) admitted that they obtained drugs supplies from drug dealers. Analysis of drug using pattern reveals that syabu (75.6 percent) and heroin (61.3 percent) are the most popular drugs used by the inmates. Finding also showed that majority (60.5 percent) of drug inmates engaged in moderate level of family relationship. Findings from this research yielded wide implications to improve drug abuse treatment and rehabilitation programs in an institution, particularly among women drug users in Malaysia.
Keywords: Drugs inmates; women; the experience of drug addiction; family relationships